PELAKSANAAN KEBIJAKAN SUPERVISI PENGAWAS PAI SMA DI KABUPATEN REMBANG - Anisah Anisah (Tarbawi : Jurnal Pendidikan Islam, 2017)
This research aims to finding: 1) the implementation of supervisory dutiesof islamic education supervisors of senior high school 2) the implementation of supervisory function of islamic education supervisors of senior high school 3) the implementation of supervisory authority of islamic education supervisors of senior high school. 4) the implementation of supervisory responsible of islamic education supervisors of senior high school. This research applied descriptive qualitative approach. The research was conducted in district Rembang for 4 months. The subjects of this research is supervisor of Islamic education supervisors at the senior high school in district Rembang. The informants were Islamic Education teachers at senior high school, headmasters and the staff of ministry religion. Data were collected with interviews, observation and documentation. Data were validated with triangulation techniques in source and method. Data were analyzed with interactive modelthat consist of; data collection, data reduction, data display, and conclusions. The results show that: 1)  implementation of duties, function, authority and responsibility by Islamic Education supervisors has been done in accordance with the PMA No 2 Tahun 2012 though not maximized 2) The obstacles experienced by  supervisors in academic supervision arethe lack in number of Islamic  Education supervisors personnel, the large number of teachers that should  be supervised, and the lack of intensity of supervision. 3) The solution of these problems are recruiting new supervisors, increasing the intensity of supervision at classroom visits and increasing a development programs of academic supervision for supervisors in a periodic and continuous manner. Penelitian ini bertujuan menemukan: 1)  Pelaksanaan tugas pengawas PAISMA di Kabupaten Rembang. 2) Pelaksanaan fungsi pengawas PAI SMAdi Kabupaten Rembang. 3) Pelaksanaan tanggung jawab pengawas PAISMA di Kabupaten Rembang. 4) Pelaksanaan Tanggung jawab pengawasPAI SMA di Kabupaten Rembang. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Penelitian dilakukan di Kabupaten Rembang dengan waktu penelitian selama 4 bulan. Subyek penelitian adalah Pengawas  Pendidikan Agama Islam SMA di Kabupaten Rembang. Informan penelitian adalah guru-guru PAI SMA di Kabupaten Rembang. Teknik  pengumpulan data dengan metode wawancara, observasi dan  dokumentasi. Teknik keabsahan data menggunakan triangulasi sumber  dan metode. Analisis data menggunakan analisis model interaktif,  meliputi: pengumpulan data, reduksi data, sajian data, dan kesimpulan. Hasil penelitian menunjukkan bahwa: 1) Pelaksanaan tugas, fungsi, wewenang dan tanggung jawab pengawas PAI SMA di Kabupaten Rembang  telah terlaksana sesuai PMA No. 2 Tahun 2012 meski masih belum  maksimal. 2) Hambatan yang dialami pengawas dalam supervisi adalah kurangnya tenaga pengawas PAI, banyaknya guru yang harus dibina dan kurangnya intensitas supervisi. 3) Solusi dari kendala tersebut adalah  rekrutmen pengawas baru, peningkatan intensitas supervisi kunjungan  kelas dan peningkatan program pembinaan supervisi pengawas secara berkala dan berkesinambungan.